การนำเสนอแนวทางการจัดกิจกรรมพลศึกษาสำหรับเด็กออทิสติกที่มีระดับความสามารถปานกลางในโรงเรียนที่มีการจัดการเรียนร่วมในระดับประถมศึกษา - เบญจพร คำจันทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This study aimed to; 1) study the problems and needs of organizing physical education for autism children with the moderate ability, 2) propose guidelines of organizing physical education for autism children with the moderate ability. The samples in the research consisted of chief executives group learning in health and physical education 42 People, physical education teachers 42 People, teacher special educators 42 people, and parents form 14 schools. Research instruments were used a questionnaire validity, IOC = 0.67, and reliability was 0.98, and. semi-structured interview The result found that; The overall of problems were at the high level including providing adapted physical education activities, budget allocation of the facilities, equipment, and the environment with activities for autism children. The schools needs to provide individual planning, teacher special educators and parents should be trained or attended a seminar on the subject organizing activities for children with autism The guidelines composed of; administrators should support for budget and activities planning; the chief executive and group learning in health and physical education, Physical education teachers, and Special educators need to be specialists in providing physical education adapted physical education activities and parents should participated of training and seminars with topic related to caring of autism children